2015
DOI: 10.4103/2319-4170.137767
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing fasciitis and sepsis caused by Vibrio vulnificus and Klebsiella pneumoniae in diabetic patients

Abstract: Background: Vibrio vulnificus related necrotizing fasciitis is a fatal, rapidly progressive soft-tissue infection. Necrotizing fasciitis caused by Klebsiella pneumoniae is rare, which is indistinguishable from V. vulnificus infection in the emergency room. The purpose of this study was to compare the clinical characteristics and outcome between these two pathogens in diabetic patients. Methods:Thirty diabetic patients were retrospectively reviewed over an 8-year period. Necrotizing fasciitis caused by V. vulni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The Chiayi Chang Gung Memorial Hospital is a tertiary hospital which situated on the western coast of southern Taiwan, and V. vulnificus are the most frequent causative organism of monomicrobial NF. The residents’ occupations were fishermen or farmers who were frequently associated with handling raw seafood, exposure to seawater, and contact with brackish water or soil [ 6 , 16 , 16 , 17 , 19 ]. However, Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Chiayi Chang Gung Memorial Hospital is a tertiary hospital which situated on the western coast of southern Taiwan, and V. vulnificus are the most frequent causative organism of monomicrobial NF. The residents’ occupations were fishermen or farmers who were frequently associated with handling raw seafood, exposure to seawater, and contact with brackish water or soil [ 6 , 16 , 16 , 17 , 19 ]. However, Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperbaric oxygen (HBO) therapy and vacuum assisted closure (VAC) therapy was administered in stable NF patients for improving wound healing. Soft tissue reconstructions, such as skin grafts and flap reconstruction, were done until the infected necrotic tissue was controlled and stabilized [ 6 , 16 , 19 ] (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Patients with DM constitute to 20.1% - 22.7% of all patients with sepsis ( 4 , 5 ). Distinct infections are more common in these patients, including necrotizing fasciitis, diabetic foot, mucormycosis, emphysematous infections of the gall bladder, kidney and urinary bladder, and invasive otitis externa ( 6 - 8 ). In a year round prospective cohort study, 705 adult patients who had type 1 DM, 6,712 adult patients who had type 2 DM and 18911 control patients who had hypertension without diabetes were compared regarding the incidence of infection.…”
Section: Introductionmentioning
confidence: 99%
“…A group of authors from Taiwan addressed this issue by comparing the clinical characteristics, laboratory findings, and outcome of patients suffering from NF caused by V. vulnificus to NF caused by S. aureus , 18 Aeromonas spp., 19 and K. pneumoniae . 20 They concluded that NF caused by V. vulnificus progresses more rapidly than NF caused by S. aureus or K. pneumonia e.…”
Section: Discussionmentioning
confidence: 99%